GUESS WHO'S COMING TO DINNER?, 1967 - Production Code Administration (Motion Picture Association of America. Production Code Administration records, 1967)
Includes correspondence, 1967; PCA analysis; credits and synopsis; MPAA certificate letter, October 13, 1967; reviews, 1967-1968; censor report, 1967
https://katalog.adlr.link/Record/finc-103-b2FpOmNkbTE1NzU5LmNvbnRlbnRkbS5vY2xjLm9yZzpwMTU3NTljb2xsMzAvODU3Mg